Life lines : writing transcultural adoption - McLeod, John, 1969- (London : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2015)
'The first critical study to explore narratives of transcultural adoption from contemporary Britain, Ireland and America fictions, films and memoirs made by those within the adoption'triad' or those concerned with the part and pain and possibilities of transcultural adoption.'
Introduction : transcultural adoption and adoptive being -- Secrets : Mike Leigh, Andrea Levy, Mei-Ling Hopgood -- Histories : E. R. Braithwaite, Toni Morrison, Sebastian Barry -- Traces : Hannah Pool, Buchi Emecheta, Catherine McKinley -- Bearings : Barbara Kingsolver, Caryl Phillips, Jackie Kay -- Coda : Victoria Station, 1969/2015.
Includes bibliographical references : (pages 234-240) and index.
Keywords: Interracial adoption in literature; Intercountry adoption; English literature -- History and criticism